In vitro, in vivo and in sílico studies of alkaloids against Giardia Lamblia (Research, Society and Development, 2022)
The In Silico technique selects and optimizes the choice of the best processes in a matrix of interest, while the In Vitro study is performed in Petri dishes with cell cultures. The In Vivo study provides the measurement of the effects of the species to be studied. In this case, the alkaloid will be injected both in cell cultures and in in vivo studies, to indicate toxicity, efficiency and its subsequent effects. Alkaloids or other types of compounds that generate drugs will be analyzed. Alkaloids are secondary metabolites that are characterized by being a cyclic structure with nitrogen and free electrons, being very reactive and presenting applications in the pharmaceutical and medicinal areas. Giardia Lamblia is a pathogenic protozoan whose transmission is through contaminated water and food, being responsible for the disease giardiasis, which has some symptoms such as abdominal pain, diarrhea and causes millions of deaths per year worldwide.